1994
DOI: 10.1055/s-0038-1635048
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Accuracy of a Variety of Medical Diagnostic Programs

Abstract: Abstract:Acute abdominal pain is one of the most widely studied applications of computer-aided diagnosis. The usual approach is to apply Bayes’ theorem with the assumption of conditional independence (“independence Bayes”). We compared various approaches to designing diagnostic programs for abdominal pain of suspected gynaecological origin. The methods range from statistical to knowledge-based. All programs were evaluated using a database of 1,270 cases collected retrospectively. Our results suggest that in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Similarly, in a study comparing classifiers for predicting breast cancer recurrence, Mani, Pazzani & West (1997) found that the independence Bayes model did best. Moreover, in studies of heart disease (Russek, Kronmal & Fisher, 1983), thyroid disease (Nordyke, Kulikowski & Kulikowski, 1971), liver disease (Croft & Machol, 1987), abdominal pain (Gammerman & Thatcher, 1991;Todd & Stamper, 1994;Ohmann et al, 1996), and dyspepsia (Fox, Barber & Bardhan, 1980) the independence model was a good choice. The phenomenon is not limited to medicine.…”
Section: Why the Assumption Is Not So Absurdmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, in a study comparing classifiers for predicting breast cancer recurrence, Mani, Pazzani & West (1997) found that the independence Bayes model did best. Moreover, in studies of heart disease (Russek, Kronmal & Fisher, 1983), thyroid disease (Nordyke, Kulikowski & Kulikowski, 1971), liver disease (Croft & Machol, 1987), abdominal pain (Gammerman & Thatcher, 1991;Todd & Stamper, 1994;Ohmann et al, 1996), and dyspepsia (Fox, Barber & Bardhan, 1980) the independence model was a good choice. The phenomenon is not limited to medicine.…”
Section: Why the Assumption Is Not So Absurdmentioning
confidence: 98%
“…In a comparative study of diagnostic programs for abdominal pain, Todd & Stamper (1994) said 'the usual approach is to apply Bayes' theorem with the assumption of conditional independence'.…”
Section: For Details) One Interesting Observation Made In This Studymentioning
confidence: 99%
“…Moreover, in studies of heart disease (Russek, Kronmal & Fisher, 1983), thyroid disease (Nordyke, Kulikowslu & Kulikowski, 1971), liver disease (Croft & Macho], 1987). abdominal pain (Gammerman & Thatcher, 1991;Todd & Stamper, 1994;Ohmann et al, 1996), and dyspepsia (Fox, Barber & Bardhan, 1980) the independence model was a good choice. The phenomenon is not limited to medicine.…”
Section: Why the Assumption Is Not So Absurdmentioning
confidence: 99%
“…A group from the United Kingdom studied computer-aided diagnostic programs for abdominal pain of suspected gynecologic etiology. Using a database of 1270 cases collected retrospectively, they determined that the independence BayesT method was near optimal, although they argued that the bnear-neighborsQ method might be more suitable for clinical use [8]. The benefits of having a computerbased Bayesian method of analysis of abdominal pain in a submarine without a physician have also been studied.…”
Section: Discussionmentioning
confidence: 98%